Management of Duodenal Ulcer with Gastroesophageal Reflux Disease (GERD) with Intravenous Pantoprazole - Ari Fahrial Syam; Murdani Abdullah; Marcellus Simadibrata; Dadang Makmun; Chudahman Manan; Daldiyono Hardjodisasto (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Proton pump inhibitors (PPIs) are the most effective anti secretory drugs available for controlling gastric acid acidity and volume. They are the drug of choice in the treatment for gastro esophageal reflux disease (GERD), Helicobacter pylori eradication, peptic ulcer and non steroidal anti-inflammatory drug (NSAID) gastropathy: For acute cases, an intravenous PPI is needed, especially for hospitalized patient. Recently, intravenous pantoprazole represents an alternative to intravenous histamine-2 receptor antagonists. We observed 2 patients who were treated with pantoprazole for duodenal ulcer, where one case had a complication of bleeding with a history of long term use of NSAID. After two weeks of treatment with pantoprazole, significant lesion healing from endoscopy findings was achieved in both cases. Keywords: peptic ulcer, upper gastrointestinal bleeding, proton pump inhibitors, pantoprazole